2021
DOI: 10.1093/eurheartj/ehab430
|View full text |Cite
|
Sign up to set email alerts
|

Targeting early stages of cardiotoxicity from anti-PD1 immune checkpoint inhibitor therapy

Abstract: Aims Cardiac immune-related adverse events (irAEs) from immune checkpoint inhibition (ICI) targeting programmed death 1 (PD1) are of growing concern. Once cardiac irAEs become clinically manifest, fatality rates are high. Cardio-oncology aims to prevent detrimental effects before manifestation of severe complications by targeting early pathological changes. We therefore aimed to investigate early consequences of PD1 inhibition for cardiac integrity to prevent the development of overt cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
1
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 30 publications
1
98
1
8
Order By: Relevance
“…These characteristics are also presented in 2 cases of ICI-related myocarditis demonstrating the ICI-induced autoimmunity ( Bockstahler et al, 2020 ). The study published by Michel et al (2022) reported a murine model on which anti-PD1 therapy promotes myocardial infiltration (CD4 + and markedly activated CD8 + T cells) and impaired left ventricular (LV) function. The analogous results of impaired LV function were found in patients with metastatic melanoma receiving anti-PD1 therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics are also presented in 2 cases of ICI-related myocarditis demonstrating the ICI-induced autoimmunity ( Bockstahler et al, 2020 ). The study published by Michel et al (2022) reported a murine model on which anti-PD1 therapy promotes myocardial infiltration (CD4 + and markedly activated CD8 + T cells) and impaired left ventricular (LV) function. The analogous results of impaired LV function were found in patients with metastatic melanoma receiving anti-PD1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The analogous results of impaired LV function were found in patients with metastatic melanoma receiving anti-PD1 therapy. Remarkably, they found that the blockade of TNFα preserved the LV function without attenuating the anti-cancer efficacy of anti-PD1 therapy ( Michel et al, 2022 ). Finally, the study of Finke et al (2021) found leukocytic infiltration (CD3 + and CD8 + cells) in cardiac biopsies from patients with ICI-associated myocarditis and the upregulation of IFN-ƴ pathway, which may indicate a possible link to the inflammasome activation and M1 macrophages activity( Fujiwara et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental data point to the hypothesis that anti-PD-1 therapy induces a smouldering disruption of cardiac immunity towards an inflammatory phenotype, with manifest consequences on cardiac function in the presence of a second hit, in the form of systemic stress induced by presence of a tumor ( 199 ). This also indicates the possibility that the inflammatory phenotype raises the risk for the development of myocarditis upon exposure to additional, yet unknown risk factors ( 200 ). Furthermore, treatment with anti-PD-1 may first produce only a latent inflammatory involvement associated to dysregulated cardiac metabolism that may progress to overt myocarditis in a subset of patients ( 200 , 201 ).…”
Section: Clinical Manifestations Of Ici Associated Autoimmunitymentioning
confidence: 99%
“…Cardiotoxicity due to antineoplastic therapy is induced by multiple factors, mainly including oxidative stress ( 99 ) [OS; including mitochondrial functional impairment ( 100 ), myocardial apoptosis ( 101 , 102 )], microtubule dysfunction ( 103 , 104 ), and disruption of myocardial immune homeostasis ( 105 , 106 ).…”
Section: Early-onset and High-incidence Cardiovascular Risks Of Cance...mentioning
confidence: 99%